#### Answer

(1;-2)

#### Work Step by Step

vertex formula -b/2a
-(-10)/2(5) = 1
Substitute x = 1 into equation 5x^2 - 10x + 3
Therefore y = -2

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

(1;-2)

vertex formula -b/2a
-(-10)/2(5) = 1
Substitute x = 1 into equation 5x^2 - 10x + 3
Therefore y = -2

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.